Purificação do ácido clavulânico por processo de filtração tangencial, extração por sistema de duas fases aquosas e re-extração com resina de troca iônica - Silva, Clóvis Sacardo da (2010)
Clavulanic acid is a β-lactam substance with low antibiotic activity. Nonetheless, it is an important medicine which acts as a potent β-lactamase inhibitor. These enzymes catalyze the hydrolysis of β-lactam ring of antibiotics, leaving them without antibiotic action. It is industrially produced with submerged cultures of Streptomyces clavuligerus, a filamentous bacterium. Extraction and purification studies have shown a very clear and defined course, when it comes to the stages that precede precipitation and crystallization. The extraction processes with ultrafiltration membranes, with organic solvents and extraction in aqueous two-phase systems (ATPS) have been studied whereas purification has been studied for processes which involve ion exchange. However, there are few works related to clavulanic acid aqueous two-phase system extraction and they are not conclusive. The present study proposed utilizing the aqueous two-phase system (ATPS) to purify the clavulanic acid and re-extract it with ion exchange adsorption, which might provide information for further studies on coupled processes which operate continuously. The first technique evaluated to re-extract the clavulanic acid was the separation process with membranes, and its results showed a low separation between PEG and clavulanic acid. In a second step, the ion exchange chromatography technique with Amberlite IRA-400Cl and Streamline Q XL resins was used. It was evidenced by the ion exchange chromatography that the Amberlite IRA- 400Cl resin makes the process of re-extraction of clavulanic acid from the top phase possible and that the phosphate present in the top phase makes clavulanic acid adsorption difficult for both studied resins. Addition of ethanol, in order to precipitate the phosphate salts, made the re-extraction of clavulanic acid from the ATPS top phase by Streamline Q XL resin possible. The third step of the global process was the optimization of clavulanic acid extraction using the aqueous two-phase systems. The results showed that it is possible to obtain yields around 100% and a purification factor of 1.5 times for the clavulanic acid. Another characteristic analyzed was the clavulanic acid degradation velocity in the aqueous two-phase system; it was very high at the bottom phase which was rich in phosphate salts. Trials of continuous aqueous twophase system process were performed. This process was shown to be operationally viable. The set of results acquired in this study will allow the study and implementation xxv of a continuous process for the purification of clavulanic acid utilizing the aqueous twophase system.